Maternal adult attachment and mother-adolescent attachment: the chain mediating role of marital satisfaction and harsh parenting - Li, Mengge; Gong, Huoliang; Zhang, Huiying; Chen, Yuping; Zhang, Chenze (Frontiers in Psychiatry, 2023)
This study explored the relationship between maternal adult attachment and mother-adolescent attachment based on the attachment theory and spillover hypothesis of family systems theory. A survey research was conducted on 992 mothers and adolescents using a convenience sampling method. A survey research was conducted on 992 Chinese mothers and adolescents using a convenience sampling method. The results indicated that (1) maternal adult attachment avoidance and anxiety were significantly negatively related to maternal marital satisfaction and mother-adolescent attachment, and significantly positively related to maternal harsh parenting; maternal adult attachment anxiety was a significant direct predictor of mother-adolescent attachment; (2) Maternal marital satisfaction and maternal harsh parenting mediated the significant effect between maternal adult attachment and mother-adolescent attachment, specifically pathways contained three: a separate mediating effect of maternal marital satisfaction, a separate mediating effect of maternal harsh parenting, and a chain mediating effect of maternal marital satisfaction and maternal harsh parenting. The findings suggest that maternal adult attachment, marital satisfaction, and harsh parenting behaviors can have significant effects on adolescents’ mother-adolescent attachment.